INFEKSI BAKTERI VIBRIO ALGINOLYTICUS PADA LUMBA-LUMBA HIDUNG BOTOL, TURSIOPS ADUNCUS YANG DIPELIHARA DI LOVINA, SINGARAJA, BALI - Johnny, Fris; Roza, Des (Research Center for Biology-Indonesian Institute of Sciences, 2014)
An experiment with the aim to identify the cause of disease in Indo-Pacific bottlenose dolphins, Tursiops aduncus was conducted in Pathology Laboratory of Institute for Mariculture Research and Development, Gondol, Bali. The diseased fish showed lost appetite, swim slowly, and haemorrhage on the body surface. These clinical signs indicate that the fish infected by bacteria. The bacteria then were isolated aseptically from different parts of fish body including chin, abdomen, dorsal and caudal fins. Some media were used to isolate the bacteria, namely Triptic Soy Agar (TSA) as a general medium, Thiosulphate Citrate Bile Salt Sucrose Agar (TCBSA) for Vibrio bacteria, Cytophaga Agar (Cyt-A) for Flexibacter bacteria, and KF-Strep Breeders media for Streptococcus bacteria. As a result, one dominant bacterium was isolated from TSA and TCBSA. No bacteria growth showed on Cyt-A and KF-Strep media.The isolate was gram-negative, fermentative, swarm on TSA, growth with yellow colony on TCBSA. Based on its characteristics the isolate identified as Vibrio alginolyticus. Minimum inhibitory concentration (MIC) against Vibrio alginolyticus were 1 ppm for Nifurpirinol, 5 ppm for Penstrep, and 10 ppm or Elbaju.